The psychological and physiological effects of making weight in international level taekwondo athletes - Langan-Evans, C. (Liverpool John Moores University, 2019)
International standard Taekwondo athletes are unique, given they are required to compete in two differing weight categories for both World (WT) and Olympic (OG) events, which have some of the largest differences amongst other making weight combat sports. Typically, this demographic will lose body mass (BM) via acute and chronic methods, in order to make the lower limit of a category. Despite a raft of literature examining the frequency, magnitude, occurrence and influences of these practices, the motivations to engage in this convention are still largely unknown. Additionally, few studies have investigated this population for both body composition and activity energy expenditures (AEE), utilising either criterion or field based measurement tools during periods of BM loss and as such, these athletes may be susceptible to low energy availability (LEA) leading to relative energy deficiency in sport (RED-S). Therefore, the main aim of this thesis was to examine the psychological and physiological health and performance consequences of making weight in international standard Taekwondo athletes. Study 1 examined the frequency, magnitude, occurrence and influences of BM loss and making weight practices, in a cohort of 106 male and female Cadet, Junior and Senior Taekwondo athletes, directly after a weigh in at a major national championships. In agreement with previous research, there were no differences between sexes, however, for the first time this study highlighted key disparities in the frequency, magnitude and occurrence of BM loss and making weight practices between age groups. Additionally for the first time, the magnitudes between WT and OG weight category requirements were elucidated, showing relative BM losses which are far higher than previously characterised in this demographic. This study also highlighted the key stakeholder groups influencing the engagement in these practices, which in younger age groups was shown to be predominantly parents. Finally, it was conveyed that the nutritional and ergogenic dietary supplement knowledge of this group was largely poor when compared to optimal guidelines. In Study 2, semi structured interviews were conducted with the key stakeholder groups (5 athletes, 5 coaches, 5 parents), as identified in Study 1. Again, high magnitudes of BM loss were described by all stakeholders in agreement with Study 1. Furthermore, each stakeholder group described their perceptions of the making weight process, with all expressing it can negatively affect health and performance, but was necessary to enhance advantages in competition. The nutritional and ergogenic dietary supplement knowledge of all stakeholder groups was poor as described in Study 1. All stakeholders agreed that education, targeted particularly at the coaches, alongside improvements in national and global federation making weight policies, were required to improve current practice. Study 3 investigated the requirements of BM losses between the OG and WT categories in 18 international standard Taekwondo athletes, within 4 days prior to a competition weigh in. This emphasised the need to engage in extreme making weight practices in order to meet elected OG category allowances, as described in Studies 1 and 2. Additionally, the body composition of these athletes was examined utilising both dual x-ray absorptiometry (DXA) and various sum of skinfold (SSKf) fat mass percentage (FM%) equations. For the first time, this study highlighted body compositional differences between athletes of varying weight categories, where all of the cohort had low FM% (< 11%). This study also demonstrated that only two of ten identified SSKf FM% equations compared favourably in parallel to the criterion measurement of DXA, for the examination of body composition within this demographic in the field. In Study 4, a laboratory simulated protocol was designed to mimic the activity profile and perceptual/physiological responses of international Taekwondo competition at various intensities. Utilising these protocols, AEE was assessed in a group of 8 male international standard Taekwondo athletes, employing both indirect calorimetry and portable actigraphy for comparison of assessment methods. AEE differed between conditions with both methods, highlighting the relevance of the various protocols for measures of workload intensity. Additionally, the portable actigraphy unit showed good agreement with indirect calorimetry, justifying its use for the measurement of AEE when utilised with this population in the field. In Study 5, a periodised nutritional and training intervention was employed with an international standard Taekwondo athlete, requiring a >13% loss of BM for competition. Utilising the findings and methods of Studies 3 and 4, energy availability (EA) was examined and measures were taken throughout to examine the potential for RED-S consequences on both health and performance parameters. The athlete successfully achieved their elected weight category limit, with minimal negative associations of RED-S syndromes exhibited on markers of metabolic, endocrine, cardiovascular, bone turnover and psychological functions. Additionally there were no negative effects apparent on either tested maximal dynamic strength/power and cardiorespiratory conditioning or competitive performances. However, post competition there was a significant rebound hyperphagic response, congruent with BM overshoot and despite the success of the intervention, this should be given further consideration in the future. This thesis serves as a means to improve the making weight practices of international standard Taekwondo athletes, by affording the ability to examine both body composition and AEE in the field, whilst providing a safe and effective intervention to lose BM without the negative associations of RED-S. However, despite this, the findings of this thesis also serve as a call to action to the national and global governing federations, in enhancing the education of key stakeholders in this sport, whilst considering the addition of more weight categories to reduce the incidence of extreme and dangerous making weight practices throughout older age divisions.